KUALITAS LAYANAN TIKET ELEKTRONIK TERHADAP KEPUASAN KONSUMEN - Rezki Orientani; Helni Mutiarsih Jumhur (Faculty of Economic and Business, University of Pasundan, 2017)
PT. Kereta Api Indonesia has transformed business and information technology applied to electronic ticket. Based on reports complaints from July to December 2016, there were total of 31 complaints on Customer Service about electronic tickets. This research aimed to determine consumer responses about the service quality of electronic ticket and find out how much influence the service quality of electronic ticket to consumer satisfaction of PT Kereta Api Indonesia. The method used in this research was quantitative, while the purpose of the study is descriptive. The sampling technique used in this research is Non Probability Sampling by purposive sampling technique and use 384 respondents. Overall, the service quality and customer satisfaction of electronic ticket were considered good. The influence of service quality of electronic ticket to customer satisfaction was amounted to 55.2%. To improve quality service, PT. Kereta Api Indonesia needs to provide a guarantee.